Effect of drying processes on nutrients and bioactive components of edible bamboo (Phyllostachys mannii Gamble) shoots growing in Meghalaya, India - Rawat, Kanchan; Chongtham, Nirmala; Bisht, Madho Singh (Journal of Postharvest Technology, 2024)
Juvenile shoots of bamboo (Phyllostachys) are the most superior quality vegetable used in various culinary purposes throughout the world. Shoots contain high moisture content and have short shelf life of 2-3 days. Thus, processing techniques are required to prevent post-harvest losses and long-term storage of shoots. In the present study, Phyllostachys mannii Gamble was subjected to different drying processes i.e. freeze (-55ºC for 24 hrs), oven (60ºC for 24 hrs) and sun (32-40ºC for 16 hrs) to select the best drying method in terms of retention of nutrients and bioactive components. Results indicated that shoots had high amount of protein, minerals, amino acids, dietary fiber, phenols and phytosterols and low amount of fat, vitamin E. Fourteen minerals and twenty amino acids were detected, of which minerals namely K, P, S, Mg, Si, Fe, Zn and amino acids namely asparagine, tyrosine, valine and leucine were found in abundant. Results showed that freeze drying was better in retaining maximum amount of macronutrients, amino acids, dietary fibers and phenols. However, sun drying was effective in retaining maximum amount of macrominerals except K, Cl, Na and microminerals which showed no significant variation in sun and freeze-dried samples.